Disc Herniation and Cyst Gas: A Rare Association Causing Radicular Compression - Mandour, Cherkaoui; Gazzaz, Miloudi; Mostarchid, Brahim el (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2017)
Introduction Intraspinal gas is a common clinical finding, but an epidural gas pseudocyst in association with lateral disc herniation compressing a nerve root is an exceptional observation.Case Report A 49-year-old man was admitted to our department presenting with sciatica. The neurological examination demonstrated moderate lumbar pain without neurological deficit. A lumbosacral computed tomography showed the presence of degenerated disc herniation and epidural gas collection.Discussion The pathological association between the cyst and the hernia is probably due to the migration of gas pumped from the intervertebral space through a breaking point or lower in the annulus fibrosis, involving its contiguity with the herniated disc.Conclusion An association between a disc herniation and a gas pseudocyst can be a cause of sciatica.
Keywords: disc herniation; gas pseudocyst; sciatica